Detection and identification of loss of efficiency faults of flight actuators - Ossmann, Daniel; Varga, Andras (Zielona Góra: Uniwersytet Zielonogórski)
We propose "linear parameter-varying" (LPV) model-based approaches to the synthesis of robust "fault detection and diagnosis" (FDD) systems for "loss of efficiency" (LOE) faults of flight actuators. The proposed methods are applicable to several types of parametric (or multiplicative) LOE faults such as actuator disconnection, surface damage, actuator power loss or stall loads. For the detection of these parametric faults, advanced LPV-model detection techniques are proposed, which implicitly provide fault identification information.
Keywords: aerospace engineering; fault detection and diagnosis; loss of efficiency type of faults; flight actuator faults